Fröplacering vid hög såhastighet - Väderstad Rapid jämfört med Amazone Cirrus - Örde, Jonas; Rehn, Anders (2009)
In today's agriculture efficiency and the capacity of tools and machinery are crucial. In this work we investigate whether it is possible to enhance the capacity of sowing by increasing the work speed of seeders, how seed technology affects seed placement, and if there is any difference between two different brands of seeders and their sow techniques. The seeders we have chosen to compare are Väderstad Rapid drill and Amazon Cirrus drill. The tillage capacity of the seeders and their traction power needs were examined as well. Väderstad Rapid and Amazon Cirrus were tested in a randomized block design with four replicates at three different speeds, 8 km/h, 12 km/h and 15 km/h. The seed placement at the different speeds was examined by dividing the seedbed into four different zones from its surface to its bottom. The soil in these zones was thereafter removed and sieved. The kernels were counted in the different zones to investigate if there were any differences between how the seeders placed the seeds at different work speeds. The experiment took place on a farm in southern Sweden, with clay content between 50-53 percent. After the sowing process, a soil survey was made in which all loose soil from a test area of 0.5 m2 on the seedbed was removed and screened through different sieves to examine the sizes of the aggregates. Possible differences in aggregate size at the three different work speeds were examined as well. The aggregates were then divided into further units; larger than 5 mm, between 2 and 5 mm, and less than 2 mm. The experiment indicates that higher work speed causes slightly higher proportion of aggregates larger than 5 mm in the seedbed, compared to lower work speeds. The proportion of small aggregates is still great enough to maintain a good seedbed. Considering seed placement at different speeds, a significant difference between Väderstad Rapid and Amazon Cirrus seed placement in zone 4 was found. At the different speeds, Väderstad Rapid placed 95-98% in zone 4 compared to Amazon Cirrus with 63-82% in zone 4. Dry weather between the sowing and the emergence calculation gave Väderstad Rapid a better result because it placed a greater number of kernels at the bottom of the seedbed compared to Amazon Cirrus. A simple test of traction power of the seeders was also made, and the results show that Väderstad Rapid worked considerably more heavy and thus needed more traction power than Amazon Cirrus. In the traction power survey no measuring instruments were used and various tractors were used as well. Because of the method the results could only be a rough valuation as the power of the tractors was not measured exactly. The results of the experiment indicates that when using Väderstad Rapid one can increase the sowing capacity by an increased work speed and still maintain good seed placement. However, there are sufficient of aggregates with a size of 5 mm or smaller in the seedbeds with both Väderstad Rapid and Amazon Cirrus.